Proposals to expand the coverage of Child Mental Health in Chile - Zúñiga Fajuri, Alejandra; Zúñiga F., Mónica (Acta Bioethica, 2020)
Early life experiences can make an important impact in the architecture of the infant’s brain, which can strengthen or weaken it permanently. The childhood psychological symptomatology is not fleeting, so early intervention involves direct social and economic benefits. This paper offers, based on the most recent findings, the addition of new Health Care Guarantees specifically aimed to treating mental pathologies in childhood. This public policy has been shown to be highly efficient and capable to make a real contribution to the reduction of both, the costs associated with Mental Health and the equity gaps in child health care.